A new cytotoxic daphnane diterpenoid, rediocide G, from Trigonostemon reidioides - Atchara Tempeam (2018)
Rediocide G (7), a new daphnane diterpenoid, was isolated from the roots of Trigonostemon reidioides (Euphorbiaceae), together with two congeners, rediocide A and rediocide B, (+)-syringaresinol, scopoletin, tomentin and stigmasterol. The structure of the new natural product was elucidated by comparison of its NMR and mass spectral data with those of previously known rediocides and confirmed by extensive 2D NMR spectral analysis. Rediocide G (7) was found to be cytotoxic to various cancer cell lines. © 2005 Pharmaceutical Society of Japan.